Factors influencing the acceptance of self-checkout machines in the supermarket industry in Singapore. - Xia, Chua Bi; Talib, Ameen (IJRDO - Journal of Applied Management Science, 2017)
The purpose of this paper is to study the factors influencing the acceptance of self-checkout kiosks inthe supermarket industry in Singapore. In particular, it is to find out whether social pressure, selfefficacy,technology anxiety and differential waiting time affects the self-checkout kiosks’ usagedecision. A simple random sample of 72 usable respondents had been obtained to test the nine differenthypotheses conceived. In conclusion, differential waiting times affect whether shoppers will use the selfcheckoutkiosks. Findings show that societal factors such as individualism and uncertainty avoidance,and demographic factors such as age and educational level plays a part in determining the levels of socialpressure, self-efficacy and technology anxiety, which affect whether the shoppers will use the selfcheckoutkiosks.